EFEKTIVITAS KEGIATAN EKSTRAKURIKULER SENI TARI DALAM MENGEMBANGKAN EKSPRESI DIRI ANAK USIA 5-6 TAHUN DI TK CENDANA MAWANG - Resa Anggreni Syam; Wahyuni Wahyuni; Umi Kusyairy; Muchlisah Muchlisah; Ade Agusriani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The results of the study indicate that extracurricular dance activities are carried out through the stages of basic movement training, rhythmic accuracy, body expression training, and final performances. Supporting factors for this activity include teacher and parental support, adequate school facilities, and high student interest. Inhibiting factors include limited practice time and differences in each child's ability to follow the movements. The implications of this activity are seen in improving children's self-expression, such as increased self-confidence, nonverbal communication skills, courage to perform in public, movement creativity, and the ability to control body coordination, its validity using triangulation of sources, techniques, and time.